On a Crucial Problem in Probabilities and Solution - Mugur-Schachter, Mioara (2008)
First the crucial but very confidential fact is brought into evidence that, as Kolmogorov himself repeatedly claimed, there exists no abstract theory of probabilities, simply because the factual concept of probability is itself unachieved: it is nowhere specified how to construct the factual probability law to be asserted on a given physical random phenomenon. Then an algorithm of semantic integration is built that permits to identify this factual probability law.Comment: 22 pages. Accepted for publication in Information And Computatio